Antigen Sampling CSF1R-Expressing Epithelial Cells Are the Functional Equivalents of Mammalian M Cells in the Avian Follicle-Associated Epithelium - Balic, Adam; Chintoan-Uta, Cosmin; Vohra, Prerna; Sutton, Kate M.; Cassady-Cain, Robin L.; Hu, Tuan; Donaldson, David S.; Stevens, Mark P.; Mabbott, Neil A.; Hume, David A.; Sang, Helen M.; Vervelde, Lonneke (Frontiers in Immunology, 2019)
The follicle-associated epithelium (FAE) is a specialised structure that samples luminal antigens and transports them into mucosa-associated lymphoid tissues (MALT). In mammals, transcytosis of antigens across the gut epithelium is performed by a subset of FAE cells known as M cells. Here we show that colony-stimulating factor 1 receptor (CSF1R) is expressed by a subset of cells in the avian bursa of Fabricius FAE. Expression was initially detected using a CSF1R-reporter transgene that also label subsets of bursal macrophages. Immunohistochemical detection using a specific monoclonal antibody confirmed abundant expression of CSF1R on the basolateral membrane of FAE cells. CSF1R-transgene expressing bursal FAE cells were enriched for expression of markers previously reported as putative M cell markers, including annexin A10 and CD44. They were further distinguished from a population of CSF1R-transgene negative epithelial cells within FAE by high apical F-actin expression and differential staining with the lectins jacalin, PHA-L and SNA. Bursal FAE cells that express the CSF1R-reporter transgene were responsible for the bulk of FAE transcytosis of labelled microparticles in the size range 0.02-0.1 µm. Unlike mammalian M cells, they did not readily take up larger bacterial sized microparticles (0.5 µm). Their role in uptake of bacteria was tested using Salmonella, which can enter via M cells in mammals. Labelled Salmonella enterica serovar Typhimurium entered bursal tissue via the FAE. Entry was partially dependent upon Type III secretion system-1. However, the majority of invading bacteria were localised to CSF1R-negative FAE cells and in resident phagocytes that express the phosphatidylserine receptor TIM4. CSF1R-expressing FAE cells in infected follicles showed evidence of cell death and shedding into the bursal lumen. In mammals, CSF1R expression in the gut is restricted to macrophages which only indirectly control M cell differentiation. The novel expression of CSF1R in birds suggests that these functional equivalents to mammalian M cells may have different ontological origins and their development and function are likely to be regulated by different growth factors.